SOSIALISASI PENGEMBANGAN EKOWISATA DAN KEWIRAUSAHAAN PRODUK LOKAL DI DESA LENEK RAMBAN BIAK, KABUPATEN LOMBOK TIMUR - Immy Suci Rohyani; Rachmawati Noviana Rahayu; Isrowati Isrowati; Ernawati Ernawati (Universitas Mataram, 2022)
The development of the village's potential to become an ecotourism village is a form of community and government effort to improve the local communities. Lenek Ramban Biak Village is one of the villages in East Lombok Regency which has the potential to become an ecotourism village. Lenek Ramban Biak Village is one of the villages in East Lombok Regency which has the potential to become an ecotourism village. The development of natural tourism potential, cultural tourism and religious tourism aims to attract tourists. Socialization of ecotourism development and local product branding entrepreneurship needs to increase knowledge and community involvement in managing ecotourism villages in the future. Aims to determine the increase in knowledge and awareness of the people of Lenek Ramban Biak Village regarding ecotourism, as well as increasing knowledge related to entrepreneurship in branding local products after socialization activities. The method used is presentations using Power Point (PPT) and question and answer discussions with socialization participants. The implementation of the activity consists of 4 stages, consist of: 1) the preparatory stage; 2) the stage of dissemination of socialization events; 3) implementation stage; and 4) evaluation stage. Socialization of activities is carried out by elaborating ecotourism materials and entrepreneurship branding of local products by resource persons. Discussions and questions and answers regarding the potential of ecotourism and community involvement in tourism management. Map the potential for natural tourism, religious tourism, cultural tourism, and culinary tourism. Data collection on local products that need branding such as bricks and traditional food. Discussion regarding product branding procedures and studies of examples of well-known products. Evaluation of socialization activities is based on the results of distributing questionnaires before and after the activity is carried out. The evaluation results show an increase in knowledge and awareness related to ecotourism by 13.5% and product branding by 17%. Community knowledge and awareness related to ecotourism increased by 13.5% and knowledge related to local product branding increased by 17%.